Protective effects of an anti‐melanocortin‐4 receptor scFv derivative in lipopolysaccharide‐induced cachexia in rats. Issue 1 (22nd August 2012) - Peter, Jean-Christophe; Rossez, Hélène; Weckering, Marjorie; Zipfel, Géraldine; Lecourt, Anne-Catherine; Owen, Joshua B.; Banks, William A.; Hofbauer, Karl G.
Abstract : Background: Cachexia is a complex syndrome defined by weight loss due to an ongoing loss of skeletal muscle mass with or without loss of body fat. It is often associated with anorexia. Numerous results from experimental studies suggest that blockade of the melanocortin‐4 receptor (MC4R) could be an effective treatment for anorexia and cachexia. In a previous study, we reported the basic pharmacological properties of a blocking anti‐MC4R mAb 1E8a and its scFv derivative in vitro and in vivo. Methods: In the present study, we further characterized the mode of action of the 1E8a scFv, evaluated its pharmacokinetic properties in mice, and assessed its therapeutic potential in a lipopolysaccharide (LPS)‐induced cachexia model in rats. Results: In vitro, scFv enhanced the efficacy of the endogenous inverse agonist Agouti‐related protein. After intravenous (i.v.) administration in mice, the scFv penetrated the blood–brain barrier (BBB) and reached its central sites of action: the scFv brain–serum concentration ratios increased up to 15‐fold which suggests an active uptake into brain tissue. In telemetry experiments, i.v. administration of the scFv in rats was well tolerated and only induced slight cardiovascular effects consistent with MC4R blockade, i.e., a small decrease in mean arterial pressure and heart rate. In the model of LPS‐induced anorexia, i.v. administration of scFv 1E8a prevented anorexia and loss of body weight. Moreover, it stimulated a myogenic response which may contribute to the preservation of muscle mass in cachexia. Conclusion: The pharmacological profile of scFv 1E8a suggests its potential value in the treatment of cachexia or anorexia.